Technical and Economic Analysis of a Robotic Station for Assembling the FPV Drone Body - Górski Marcin; Prykhodzhenko Valerii; Karamon Tomasz; Caban Jacek (Logi)
The current technological progress is possible due to automated assembly and transport operations, and the increasing use of robotic cells. This article presents a robotic station for assembling the body of an FPV drone. The article uses analyzes and simulations as well as the results of simulation studies. The research has shown that the robotic station significantly increases the efficiency of the assembly process compared to traditional methods, shortening the unit production time by approximately 30-50%. The economic analysis has shown that despite higher initial costs, the investment in a robotic station pays off in approximately 3.3 years, which results from lower operating costs and the elimination of some labor costs. Moreover, the automation of assembly processes not only contributes to financial savings, but also to the improved quality of the final product. The future research should focus on further optimization of robotic stations, in particular on increasing their flexibility and adaptability in dynamic production environments.